Revisiting Nasal Reconstruction After Mohs Surgery: A Simplified Approach Based on the Liberal Application of Local Flaps. Issue 3 (September 2019) - Vasilakis, Vasileios; Nguyen, Khang T.; Klein, Gabriel M.; Brewer, Bruce W.
Abstract : Introduction: Nasal reconstruction after oncologic resection often constitutes a technically demanding task. The aim of this study was to investigate our experience with nasal reconstruction after Mohs micrographic surgery using the following 3 well-established, versatile, and reliable techniques: the bilobed flap, nasolabial flap, and forehead flap. Methods: A single-surgeon retrospective chart review of all patients undergone a bilobed, nasolabial, or forehead flap for nasal reconstruction after Mohs micrographic surgery from 2003 to 2017 was conducted. Data collected for analysis included demographics and defect characteristics. Revisions and complications were analyzed. Results: A total of 83 patients were included in the study; 52 patients underwent bilobed, 17 patients nasolabial, and 14 patients forehead flaps. All defects involved the middle and lower nasal zones. There was a significant difference in the defect size between the 3 groups ( P < 0.001). The mean diameters were as follows: 1.37 cm for the bilobed, 2.22 cm for the nasolabial, and 3.46 cm for the forehead flap groups. Liberal utilization of the bilobed and nasolabial flaps achieved reconstruction of defects larger than typically described in the literature. Reconstruction of all defects, including support for successful restoration of mucosal lining and cartilage when indicated, was achieved. An algorithm dealing with defects larger than 0.5 cm in the middle and distal nasal zones was devised. Conclusions: In this study, the liberal application of the 3 flaps was described based on an individualized treatment approach. The algorithm provides a simplified approach for larger nasal defects in the middle and lower thirds.